Auditoría financiera y su incidencia en la liquidez de la cooperativa interprovincial de transportes terrestres “Flota Bolívar” cantón Quevedo, año 2014 - Tigre Mendoza, Jimena Lisseth (2015)
Navigate the conveyance of passengers is no easy task due to the high competition in the sector and the existence of new regulatory rules establishing requirements and provisions involving specific systems within the activity of the carrier. This is represented in a financial audit to measure compliance and internal controls in these areas, therefore the evaluation of the working papers for a relatively reasonable assurance opinion and issue the final audit report. This research was conducted in the Canton Quevedo, Los Rios Province, the same as its main objective Perform Financial Audit and its impact on the liquidity of the Interprovincial Cooperative Land Transport "Fleet Bolívar" Quevedo Canton, Year 2014 methods and techniques used were interviews and observation, which allowed to obtain first-hand information and by diagnosing main activities of the audit and determine compliance with the procedures established by the company and the reasonable assurance of financial information. Therefore, this paper presents a financial audit for the period 2014 to the transport of passengers "Fleet Bolívar" which follows the step of communicating results is noted that includes finding found on the poor internal control with indicators, conclusion, recommendation and opinion of the legal base, working papers which the veracity of financial statements verified by detailing an opinion on the fairness of the financial statements and all documents held that support the report. Finally, they acknowledge the conclusions and recommendations of the thesis, which will help the company for successful decision making.